Opioid‐free anesthesia for patients undergoing mastectomy: A matched comparison. Issue 9 (6th August 2020) - King, Caroline A.; Perez‐Alvarez, Idanis M.; Bartholomew, Alex J.; Bozzuto, Laura; Griffith, Kayla; Sosin, Michael; Thibodeau, Renee; Gopwani, Sumeet; Myers, Joseph; Fan, Kenneth L.; Tousimis, Eleni A.
Abstract: Opioid‐free anesthesia (OFA) is being implemented in breast surgery due to increased awareness of adverse effects and the national opioid crisis. The objective of this study was to examine the effect of OFA on postoperative pain and postoperative nausea and vomiting (PONV) in mastectomy patients. A single‐institution matched‐cohort study was conducted from 2014 to 2017 on 48 women undergoing mastectomy, with the majority also undergoing immediate prosthetic‐based reconstruction. Patients received either conventional anesthesia (CA) or a novel OFA regimen. Primary outcomes included postoperative pain scores, opioid use, and need for antiemetics that were evaluated both in the PACU and on the hospital floors. No significant differences were found in PACU opioid or antiemetic use between OFA and CA. Pain scores in PACU and on POD0 were not significantly different. There was a significant but modest decrease on POD1 in OFA patients (3.9 vs. 5.1, P  = .046). Additionally, patients with higher intraoperative opioid regimens experienced significantly increased PONV ( P  = .023). This study demonstrated the efficacy of OFA in controlling postoperative pain and nausea compared to a traditional opioid‐based regimen. Regardless of intraoperative opioids, patients experienced similar postoperative opioid requirements and PONV with decreased pain scores. Thus, OFA is feasible in mastectomy patients and should be further evaluated in select patients.